Immagini migranti, immagini in-discriminanti Latenze e valenze nell’uso di foto e filmati in ambito migratorio - Alberto Baldi (EtnoAntropologia)
Pictures, stereoscopies and films were some of the tools that the emigrants used, when they could afford them, as a form of support or an alternative to the exchange of letters. They were a mean to better define their new status of citizens of the world, who freed themselves from the poverty of the rural and southern contexts they left. The fixed, stentorian lapidary and three-dimensional image depicted in these portraits, seemed to provide the illusion to cross the threshold of overseas metropolis or of any other place on earth. It was a cinematographic image, therefore one in motion, in the end a more realistic picture which gave to the emigrants the opportunity to show off the success of their migratory project, had it actually been realized or not. They gathered from the urban contexts where they settled down, all the necessary and technological know-how to convey, sometimes autonomously, as an amateur photographer or film maker, the winning image they wanted to send back home and project on the village walls on occasion of one of their “well planned” trips back. On these occasions, once again, the picture was necessary to strengthen their image of successful people. If on one side they meant to mark the distance from their fellow coutrymen, who had remained back at the village, at the same time they considered them as the recipients of their visual messages; denoting hence, the continuing of a relationship with them. Through the study of some cases dating back to the first half of the twentieth century, in several parts of the Italian region of Basilicata, we try to make an analysis of the specific visual and audiovisual languages adopted by some emigrants whose aim was to portray an image of themselves described with an extreme care and meant to fuel a dynamic of both parting and approaching their place of origin.